InfraNodus analysis of text, networks, and sentiment on a political actor across media platforms - Lawelai, Herman; Nurmandi, Achmad; Maulana, Harry Fajar; Jubba, Hasse (Program Studi Ilmu Komunikasi, 2025)
This study examines how public perceptions of Anies Baswedan are shaped through YouTube, Twitter, and Google, employing text, network, and sentiment analysis with InfraNodus. Data was collected through each platform's official API with a focus on the keyword